Growth and yield of rapeseed (Brassica campestries var. toria) influenced by NPK and sulphur under rainfed condition - Anjali Basumotary,; Nayan Jyoti Ojha,; Mahima Begum, (Journal of Oilseed Brassica, 2026)
field experiment was conducted during two consecutive years, 2016-17 and 2017-18 in the Rabi season at InstructionalCum Research Farm of Assam Agricultural University, Jorhat, Assam, India to find the effect of different fertilizer (NPK)and sulphur (S) levels on growth and yield of rapseed (Brassica campestries var. toria). The experiment comprised of 3levels of NPK viz. F 1: 30.00-26.25-11.25 kg N- P2O5 - K2O/ha (75% of RDF), F2: 40.00-35.00-15.00 kg N- P2O5 - K2O/ha (100%of RDF), F3: 50.00-43.75-18.75 kg N- P2O5 - K2O/ha (125% of RDF) and 5 levels of sulphur viz. S 1: 0 kg S ha-1, S2: 5 kg S ha-1, S 3: 10 kg S ha-1, S4: 15 kg S ha-1, and S5: 20 kg S ha-1 . Result revealed that all the growth characters as well as yieldattributing characters increased with increasing level of NPK upto 50.00-43.75-18.75 kg N-P2O5-K2O (125% of RDF) butat par with 40.00-35.00-15.00 kg N-P2O5-K2O (100% of RDF). Similarly, the highest seed yield of 824.53 kg ha-1 and 799.3kg ha-1 during 2016-17 and 2017-18 was recorded by application of 125% of RDF which was at par with the yield (796.60kg ha-1, 766.40 kg ha-1) obtained from 100% of RDF. Similar trend was also observed in case of stover yield, oil contentand oil yield. Moreover, with increase in dose of sulphur from 0-20 kg ha-1 all the growth characters viz., plant height,number of branches per plant and leaf area index were increased and the highest seed yield (910.89 kg/ha, 885.49 kg/ha)was recorded with the application of 20 kg S ha-1 in both the years.